2011
DOI: 10.1890/es10-00150.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between groundwater use, water table, and recovery of willow on Yellowstone's northern range

Abstract: Abstract. Excessive levels of herbivory, incision of stream channels, and climate warming are believed to be responsible for the decline of woody deciduous plants in riparian zones in western North America, declines that are likely to be associated with diminished biological diversity. In the northern elk wintering range of Yellowstone National Park, USA, overbrowsing by elk (Cervus elaphus), lowered water tables resulting from stream incision, and loss of activity by beaver (Castor canadensis) have been impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…However, increased availability of water offers a plausible mechanism for these responses for two reasons. Photosynthetic rates of willows on undammed plots with deep water tables were limited by water availability [49], and isotopic analysis of water use by willows adjacent to our plots showed clear positive correlations between height and access to groundwater [24]. Tercek et al [50] observed that tall willows had twice rspb.royalsocietypublishing.org Proc R Soc B 280: 20122977…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, increased availability of water offers a plausible mechanism for these responses for two reasons. Photosynthetic rates of willows on undammed plots with deep water tables were limited by water availability [49], and isotopic analysis of water use by willows adjacent to our plots showed clear positive correlations between height and access to groundwater [24]. Tercek et al [50] observed that tall willows had twice rspb.royalsocietypublishing.org Proc R Soc B 280: 20122977…”
Section: Discussionmentioning
confidence: 65%
“…), by a population of elk (Cervus elaphus) released from control by predators [16][17][18][19][20]. However, it remains unclear if restoration of wolves has restored the riparian zone via a trophic cascade [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Willows use soil water when it is available early in the growing season and deeper ground water later in the summer (Johnston et al 2011). Groundwater use by willows in Yellowstone National Park was not correlated with water table depth, and plants consistently used primarily ground water at sites with a water table deeper than 140 cm (Johnston et al 2011).…”
Section: Historic Analysismentioning
confidence: 92%
“…A fundamental difference in riparian willow and upland forest tree species decline is due to willows being phreatophytes whose primary water source is shallow ground water (Johnston et al 2011). Willows are moderately susceptible to drought stress; however, when they have access to a reliable source of ground water <3 m from the ground surface, they rarely experience hy- Note: 2011 models had identical model weights when compared with 2010 models.…”
Section: Historic Analysismentioning
confidence: 99%
See 1 more Smart Citation